2020
DOI: 10.20944/preprints202008.0284.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

<strong>How Parks Provide Thermal Comfort Perception in the Metropolitan Cores; A Case Study in Madrid Mediterranean Climatic Zone </strong>

Abstract: The combined effects of global warming and increasing urban heat islands (UHIs) on air temperature and heat stress in cities are notable physical and mental health implications for citizens. With research having shown the effective role of urban green spaces in decreasing urban heat, this study investigated the cooling effect of a large urban park on thermal comfort outside the park area, from psychological and physiological perspectives. The studied park is located in the center of Madrid and adjacent to UHI.… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…Other studies in the northern [7,[9][10][11] and western [8] sides of Retiro Park in Madrid have shown that the park cooling effect can reduce the air temperature during the summer days at a distance further from the park (Fig. 6).…”
Section: Influential Factors On Park Cooling Effectmentioning
confidence: 88%
See 3 more Smart Citations
“…Other studies in the northern [7,[9][10][11] and western [8] sides of Retiro Park in Madrid have shown that the park cooling effect can reduce the air temperature during the summer days at a distance further from the park (Fig. 6).…”
Section: Influential Factors On Park Cooling Effectmentioning
confidence: 88%
“…That is, in the northern area, the cooling effect of the park up to a distance of 665 m can reduce the air temperature compared to the area located in UHI between 0.6 and 1.3 °C [7,[9][10][11]. This effect is also able to reduce the air temperature in the western part of the park to the range of located at 855 m (adjacent to UHI) between 2.4 and 2.8 °C [8]. Owing to these changes, it is questionable that what role environmental factors play in the distance and intensity of the cooling effect of the park in its surroundings.…”
Section: Influential Factors On Park Cooling Effectmentioning
confidence: 96%
See 2 more Smart Citations